2018
DOI: 10.24106/kefdergi.357971
|View full text |Cite
|
Sign up to set email alerts
|

4-5 Yaş Grubu Çocukların Sosyal Gelişim Düzeyleri İle Öz Bakım Becerileri Arasındaki İlişkinin İncelenmesi

Abstract: İlişkisel tarama modelindeki araştırmanın amacı, okul öncesindeki 4-5 yaş grubu çocukların sosyal gelişim düzeyleri ile öz bakım becerileri arasındaki ilişkinin belirlenmesidir. Evren, Denizli İl Milli Eğitim Müdürlüğü'ne bağlı Pamukkale ilçesindeki bağımsız anaokullarındaki 4-5 yaş grubu çocuklardır. Kişisel Bilgi Formu, Davranış Değerlendirme Ölçeği ve Öz bakım Becerileri Kontrol Listesiyle veriler toplanmıştır. Sayı, yüzde dağılımları, Pearson Korelasyon, Mann Whitney U, Kruskal Wallis ve T Testleriyle veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
2
1
0
1
Order By: Relevance
“…Taşdemir Yiğitoğlu et al 38 conducted a study using the "Self-Care Skills Control List" scale on children and emphasized that female children were more advanced in meeting self-care needs such as eating and dressing compared to male children, aligning with our study. However, no significant difference was found based on gender in terms of personal care skills 38 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Taşdemir Yiğitoğlu et al 38 conducted a study using the "Self-Care Skills Control List" scale on children and emphasized that female children were more advanced in meeting self-care needs such as eating and dressing compared to male children, aligning with our study. However, no significant difference was found based on gender in terms of personal care skills 38 .…”
Section: Discussionsupporting
confidence: 84%
“…Taşdemir Yiğitoğlu et al 38 conducted a study using the "Self-Care Skills Control List" scale on children and emphasized that female children were more advanced in meeting self-care needs such as eating and dressing compared to male children, aligning with our study. However, no significant difference was found based on gender in terms of personal care skills 38 . In another study, the scores obtained from the "Social Skills Scale Based on Gender" indicated that female children (43.65) managed their emotions better than male children (39.26), supporting the idea of gender-related differences in social skills 39 .…”
Section: Discussionsupporting
confidence: 84%
“…In the research, it was found that there was no significant difference between students' misbehaviors and teachers' educational status. In the studies conducted by Dinçer and Akgün (2015), Güneş (2016), Turkish Studies -Education, 15(1) Sağlam (2018), Yüksel (2013), it is seen that there is no significant difference between teachers' educational status and classroom management skills.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Çocuklar yaşamın ilk altı yılında çok hızlı gelişmektedir. Bu dönem çocukta kişilik yapısının şekillenmeye başladığı, en önemlisi temel alışkanlıklarının kazandırılabildiği çocuğun hayatındaki en önemli dönemdir (5). Bu büyüme ve gelişme döneminde çocuğun yeme alışkanlıkları da doğrudan veya dolaylı olarak ailenin, özellikle anne ve babanın beslenme alışkanlıklarından etkilenmektedir.…”
Section: Dokuz Eylül üNiversitesi Hemşirelik Fakültesi Elektronik Der...unclassified